Subverting the Patriarchy: Gender Roles in the Poetry of Sylvia Plath - Islam, Nazrul; Sharma, Umakant (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
Sylvia Plath’s poetry emerges as a profound exploration of gender identity, psychological trauma, and rebellion against patriarchal structures. Writing during a period when women's roles were rigidly defined by domesticity and subservience, Plath uses her poetic voice to interrogate, destabilize, and reimagine these constraints. Through key works such as Daddy, Lady Lazarus, The Applicant, and Ariel, this paper examines how Plath portrays the tension between societal expectations and female autonomy. By investigating her use of metaphor, irony, and confessional voice, the article reveals how Plath's poetry critiques gender norms and articulates a powerful, if often painful, female subjectivity.